Validation of the focal cerebral arteriopathy severity score (FCASS) in a Swiss cohort: Correlation with infarct volume and outcome. (September 2020) - Slavova, Nedelina; Fullerton, Heather J.; Hills, Nancy K.; Breiding, Philipe S.; Mackay, Mark T.; Steinlin, Maja
Abstract: Background: Focal cerebral arteriopathy (FCA), a major cause of childhood arterial ischemic stroke (AIS), can progress and lead to increased infarct size and/or recurrent stroke. Evaluating treatment options depends on the ability to quantify reliably the degree of stenosis in FCA. Aims: We validated the recently introduced FCA severity score (FCASS) in an independent cohort from the Swiss Neuro-Paediatric Stroke Registry (SNPSR). Materials and methods: We included children with FCA who had MR or CT angiography and a Pediatric Stroke Outcome Measure (PSOM) at 6-months and 2-years post-stroke. A paediatric neuroradiologist applied the FCASS and the modified pediatric Alberta Stroke Program Early Computed Tomography Score (ASPECTS), a measure of infarct volume, to all available imaging. Two senior paediatric stroke neurologists and a neuroradiology fellow independently assigned FCASS scores to test interrater reliability. Pairwise correlations between FCASS, pedASPECTS, and PSOM were examined. Results: Thirty-two children [median (IQR) age = 5.9 (1.8, 9.6), 19 males] were included. The median maximum FCASS score at any time was 9 (IQR 6, 12; range 3, 16). Larger infarct volume scores correlated with both higher maximum FCASS scores and worse post-stroke outcomes, although we found no direct correlation between FCASS and outcomes. Stroke neurologists tended to assign lower FCASS scores than the neuroradiologist, but interrater reliability was predominantly good. Conclusions: In this independent validation cohort, higher maximum FCASS correlated with greater infarct volume scores that also correlated with worse neurological outcomes. Scoring by non-imaging specialists seems to be valuable, although differences are present. Highlights: Treatment trials under development for Focal Cerebral Arteriopathy (FCA)—a unilateral anterior circulation arteriopathy that causes childhood arterial ischemic stroke—require a validated metric for FCA severity. The FCA Severity Score (FCASS) quantifies disease severity and extent. The goal of the current study was to validate the FCA Severity Score in an independent cohort of FCA cases from the Swiss Neuro-Paediatric Stroke Registry (SNPSR). In this independent validation cohort, higher maximum FCASS correlated with greater infarct volume scores that also correlated with worse neurological outcomes.